DETEKSI FINANCIAL STATEMENT FRAUD DENGAN ANALISIS FRAUD TRIANGLE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Yulia Zahro; Nur Diana; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this study was to determine the effect of fraud triangle inexplaining the occurrence of financial statement fraud. Fraud triangle consists ofpressure, opportunity, and rationalization. Four variables are proxied frompressure (financial stability, personal financial need, external pressure, andfinancial targets). Two variables are proxied from opportunity (nature of industryand effective monitoring). And one last variable is proxied from rationalization.Based on logistic regression analysis there are 77 companies that commit fraud,and 31 companies that do not commit fraud during 2014-2017. From this study itcan be concluded that there is a positive influence between external pressure(LEV) on financial statement fraud, and six other variables consisting fromfinancial stability, personal financial needs, financial targets, nature of industry,effective monitoring, and rationalization has no effect on financial statementfraud. This result supports the fraud triangle theory in explaining the occurrenceof financial statement fraud.Keywords: financial statement fraud, pressure, opportunity, rationalization